Antioxidative, anti-inflammatory and antineoplastic potential of dicerocaryum species - Madiga, Maphuti Carol (University of Limpopo (Turfloop Campus), 2007)
Refer to document
Thesis (M.Sc. (Biochemistry )) --University of Limpopo, 2007
Keywords: Antioxidative potential; anti-inflammatory potential; antineoplastic potential; dicerocaryum species; 633.88; Medicinal plants -- South Africa; Herbs -- Therapeutic use